"A Methylotrophic Thermotolerant Actinomycete With a NAD+- Dependent Methanol Dehydrogenase" - S Eshraghi; Ian C Hancock; E Williams (Tehran University of Medical Sciences, 2002)
The methylotrophic thermo tolerant actinomycete strain 381, was isolated from a compost sample, assimilated methanol during growth. Methanol dehydrogenase could not be detected in cell extracts using dye-linked assays in the absence of NAD+. Dichlorophenol-indophenol-linked methanol oxidation was detected in broken cell suspensions in the presence of NAD+ and the absence of cyanide. Taxonomic studies showed that actinomycete strain 381 was distinct from Nocardia species 239, which has also been reported to contain an NAD+- dependent methanol dehydrogenase. The organism can also utilizes pyruvate, casamino acid, glucose, glycerol and many other carbon sources as described before. Preliminary enzyme studies suggested that the cell extracts contained phosphoribulokinase and (RUBP) ribulose bisphosphate carboxylase (the two key enzymes for Calvin cycle) which-compounds indicating that actinomycete strain 381, assimilates C1by the means of Serine pathway.